Regional Organizational Budget Absorption: The Role of Budget Planning, Human Resource Competence and Procurement of Goods and Services - Belisca, Apra; Azmi, Zul; Sari, Dwifiona (Asosiasi Dosen Akuntansi Indonesia, 2023)
This research examines the influence of budget planning, human resource competency, and procurement of goods and services on budget absorption. The object of this research was 40 OPDs, which were surveyed using a questionnaire. Data was processed from 63 respondents used in this research. This type of research is quantitative method research, and data is processed using multiple linear regression. The study results show that budget planning, human resource competence, and procurement of goods and services partially influence budget absorption in downstream Indragiri district regional apparatus organizations